Induksi Pematangan Gonad Ikan Lele (Clarias sp.) Menggunakan Oodev dan Kunyit (Curcuma longa) melalui Pakan di Kabupaten Tulang Bawang Barat - Agus Oman Sudrajat; Herawati Rasid (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
One important phase in the fish reproduction cycle is the gonad maturation process. In general, catfish reproduce in the rainy season and do not reproduce in the dry season.The purpose of this activity is to accelerate the reproductive performance of catfish broodstock to produce optimal seeds outside the spawning season. Efforts to obtain optimal fish seed can be done by improving the performance or reproductive performance through supplementation of nutrients in the broodstock feed and combined with Oodev hormone premix. Catfish broodstock as many as five pairs with a total weight of 17.5 kg were fed with Oodev 0.5 mL/kg and turmeric 3%/kg of feed.Feeding is done as much as 3% of the total weight of catfish broodstock with a frequency of three times a day ie at 09.00, 15.00, and 21.00 WIB. Maintenance is carried out for 4 weeks. The results of the activity showed that the administration of Oodev and turmeric were able to produce mature gonads as much as 60%.